Molecular Analysis of HS-111 and 3`HS1 Variations in β-Thalassemia Intermedia Patients with High Levels of HbF - Mohammad Hamid (Cell Journal, 2010)
Objective: To study the possible association between high levels of fetal haemoglobin(HbF) in β-thalassemia intermedia patients and HS-111 and 3`HS1 sequence variations.Materials and Methods: In this study, the 3' HS-1 and HS-111 regions of 30 ß-thalassaemiaintermedia patients (ß°/ß°) with high levels of HbF, 21 ß-thalassemia major patientsand 40 normal Iranian individuals were analyzed by single-strand conformation polymorphism(SSCP) and polymerase chain reaction (PCR) sequencing.Results: Two nucleotide variations in 3' HS111 (-21A>G) and 3`HS1 (179C>T) wereidentified. The most frequent sequence variation was 3' HS111 (-21A) in the intermediapatients and 3`HS111 (-21G) in the major thalassemia patients. In contrast to the 3`HS1marker, both 3'HS111 A and G variants showed a correlation with each studied group.Conclusion: The HS111 marker in conjunction with other parameters could be used asappropriate genetic markers to discriminate β-thalassemia intermedia patients (β°/β°) withhigh levels of HbF from β-thalassemia major patients.